Recognition of psychological comorbidity and psychotherapeutic treatment status of ventricular assist device patients - Gronewold, Nadine; Mayer, Gwendolyn; Müller, Yvonne; Levinson, Rebecca T.; Bruns, Bastian; Meyer, Anna L.; Rivinius, Rasmus; Frey, Norbert; Kreußer, Michael; Schultz, Jobst-Hendrik (Artificial organs, 2024)
Background Due to its high impact on quality of life and mental health, close monitoring and often psychotherapy is recommended for patients with a ventricular assist device (VAD). This study investigates the psychological comorbidity and the corresponding psychotherapeutic treatment situation of VAD patients. Special attention is also given to the professional perspective VAD team (assistant and senior cardiologists and specialized nurses). Methods We conducted a cross-sectional observational study. Data from 50 VAD patients (mean age = 53.52, standard deviation = 13.82 years, 84.0% male) and their VAD team were analyzed. The presence of a psychological disorder was evaluated by structured clinical interviews for DSM-IV (SCID-I-Interviews). Patients answered a questionnaire regarding their current psychotherapeutic treatment status and their attitude towards psychotherapy. The VAD team answered a questionnaire about the patients' needs for psychotherapy and indicated whether they addressed this topic with the patient. Data were analyzed descriptively, by analysis of variance and t-test. Results A total of 58% of VAD patients suffered from at least one significant psychological disorder, 79.3% of those were not in psychotherapy. The VAD team could not identify the patients who suffered from a psychological disorder (F = 1.90; p = 0.18). They perceived more need for psychotherapy than they addressed with their patients (T = 3.39; p < 0.001). Conclusions While there is a high psychological morbidity among VAD patients, only few receive psychotherapy. Psychological comorbidity is not easily detected by the VAD team. Standardized psychosocial care could be implemented by regular psychological assessments and further information of patients and their VAD teams.
Gesehen am 16.12.2024